Manifestation of Colonial Discourse and Anthropocentric Outlook in James Michener’s Hawai’i - Indriyanto, Kristiawan (OKARA: Jurnal Bahasa dan Sastra, 2020)
One of the foremost developments in literary criticism is the awareness that colonialism results in ecological devastation of the colonies through exploitation of nature. This phenomenon is legitimized through Western anthropocentric paradigm that considers nature merely as commodity to be utilized for humankind's benefit. This paper analyses the underlying Western colonial discourse that rationalizes ecological exploitation in Hawai'i based on the reading on James Michener's Hawai'i. With postcolonial ecocriticism as the framework, the present study focuses on the conflicts that arise between the islanders and the white settlers concerning human and non-human relationships. Western discourse promotes the superiority of their culture based on the privileged position in a binary opposition which is contrasted with the backwardness of the natives. The labelling of certain Hawai'ian traditions as pagan and heathen practice plays a pivotal role in articulating the Western anthropocentric paradigm in which the missionaries function as agent of colonialism. The culmination of Western colonial discourse manifests in the transformation of Hawai'ian landscape for capitalistic enterprise of agriculture and sugar plantation. This event also signifies the commodification in the landscape and centre-periphery relationship which underlines the economical exploitation of the colony.